Information experience - Bruce, Christine (Library and information science (New York, N.Y.) ;, 2014)
The German word for experience Erlebnis the experience of the life, to live through something underpins this book: making visible scholarly opportunities for richer and deeper contextualizations and examinations of the lived-world experiences of people in everyday contexts as they be, do and become. (Ross Todd, Preface). Information experience is a burgeoning area of research and still unfolding as an explicit research and practice theme. This book is therefore very timely as it distils the reflections of researchers and practitioners from various disciplines, with interests ranging across information, knowledge, user experience, design and education. They cast a fresh analytical eye on information experience, whilst approaching the idea from diverse perspectives. Information Experience brings together current thinking about the idea of information experience to help form discourse around it and establish a conceptual foundation for taking the idea forward. It therefore provides a number of theoretical lenses for examining peoplés information worlds in more holistic and dynamic ways. (Ross Todd, Preface).